An insight into the adverse drug reactions considering causality, severity, preventability and adherence among patients receiving anticancer drugs at a North Indian rural tertiary care centre - Singh, Abhay Pratap; Dixit, Alok; Singh, Chandra Veer; Mishra, Ajit Kumar; Kumar, Vishesh; Kaktan, Kapil (International Journal of Research in Medical Sciences, 2025)
Background: The cytotoxic nature of anticancer drugs and their limited therapeutic index make adverse drug reactions (ADRs) a significant challenge in therapeutics in oncology. These adverse drug reactions have a major effect on quality of life, therapeutic results and patient adherence. An estimated 1,392,179 cancer cases were reported in India in 2020, representing an incidence rate of 98.7 incidences per 100,000 people. With a prevalence of 10-12%, ADRs are more common among hospitalised and elderly patients. It is essential to comprehend the causality, severity and preventability of ADRs in order to optimise cancer treatment and enhance patient safety. Methods: An observational study was conducted at a tertiary care centre in western Uttar Pradesh. Chemotherapy patients were observed for adverse drug reactions. The Modified Hartwig and Siegel scale was used to assess the severity, the WHO-UMC scale was used to determine causality and the Schumock and Thornton criteria were used to determine preventability. Treatment adherence was also examined using Modified Morisky scale. Results: The most frequent ADRs were gastrointestinal and haematological. The majority of ADRs were categorised as moderately severe, mostly non-preventable and probable in the causation evaluation. In several instances, treatment adherence was impacted. Conclusions: ADRs from anticancer drugs continue to be a major clinical problem. Risks can be mitigated and patient safety can be enhanced with timely intervention and regular monitoring.